Análise da utilização de coberturas do tipo laje impermeabilizada executadas em Pato Branco - PR na última década - Gnoatto, Eloise Leonora (2014)
The building coverage is responsibel for the tightness, protection and comfort. Nowadays, mainly due of rising costs land and the consequent requirement for efficient use of space, the coverages composed of impermeable slab are on the rise. However, the labor’s specialization not always follows this growth. As a result, frequently problems associated with poor waterproofing causes numerous disagreements between builders and customers. Therefore, it was noted a need of a study of the use of waterproofed slabs as coverages, searching the experiences and judgements of professionals in the area, as well as the owners point of view. It was made through the apllication of questionnaires, even as monitoring the waterproofing procedures execution, thus determinig the performance of the construction process in question. At the end of the interviews, there was a union of the collected data, accompanied with an analysis of the main points mentioned. Finally, it was observed that the waterproofing slabs performed in the city of Pato Branco still has much to improve, starting with the specific design of waterproofing that although predicted by NBR 9575 (2010), is not realized. The tightness test is another missing point, since it was found that is not done in all works, leaving in doubt the efficiency of the waterproofing done. Among the anomalies perceived by users, the main causes are related to unskilled labor. Despite the adversities, the final evaluation was considered positive, with an overall satisfaction above 80%. For the professionals, the optimism related to the increment of the system utilization predominated.